Analisis Keterampilan Passing Bawah pada Siswa Ekstrakurikuler di SMA Negeri 6 Soppeng - Saka, Naufal Alif; Akbar. B, Suryadi; Tonda, Primarani Hakim; Sulfarhan, Muhammad Isfan; Fahrizal T, Muh.; Ramadhani, Maqma; Juhanis; Arfanda, Poppy Elisano (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the level of underhand passing skills in volleyball among students in the extracurricular programme at State Senior High School 6 Soppeng. The study employed a quantitative approach using a descriptive method. The study population comprised all participants in the volleyball extracurricular programme at State Senior High School 6 Soppeng, with a sample of 15 female students selected using total sampling. Data collection was carried out through underhand passing skill tests and observation sheets. The data obtained were analysed using descriptive statistics with the aid of SPSS version 20.00. The results of the study showed that 4 students (27%) were in the very good category, 5 students (33%) in the good category, and 6 students (40%) in the moderate category, whilst no students fell into the poor or very poor categories. Based on these results, the level of underhand passing skills among the volleyball extracurricular students at State Senior High School 6 Soppeng was generally in the moderate category